Perlindungan Hukum terhadap Data Nasabah dalam Transaksi Financial Technology di Indonesia - Anas Heryanto; Iksan; Nurul Izati Mardiyah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The development of financial technology has increased the processing of customers' personal data and created risks of data leakage and misuse. This study aims to analyze the legal protection of customer data and the responsibilities of digital service providers. The method used is normative legal research with both legislative and conceptual approaches. The results indicate that data protection is regulated through the Personal Data Protection Law, the Electronic Information and Transactions Law and regulations for the digital financial sector. However, its implementation remains hampered by oversight, transparency and cybersecurity. Therefore, strengthening oversight and legal accountability mechanisms is necessary to ensure effective customer data protection.